Dissemination of an internet-based program for the prevention and early intervention in eating disorders: relationship between access paths, user characteristics, and program utilization - Bauer, Stephanie; Bilić, Sally Sophie; Moessner, Markus (Zeitschrift für Kinder- und Jugendpsychiatrie und Psychotherapie, 2020)
Objective: Research on the dissemination of e-mental health interventions is in an early stage, so that little is known about the reach, costs, participant characteristics, and patterns of program utilization associated with different recruitment strategies and access paths. This study investigated differences between user groups informed about an Internet-based program for the prevention and early intervention in eating disorders via different recruitment channels. Method: Participant characteristics and user behavior of 3548 participants in the Internet-based program ProYouth were analyzed. Participants were informed about ProYouth via different channels (e.g., print materials, high school, Internet). Results: Results indicate significant relationships between access paths and both user characteristics and program utilization. Participants who were informed about ProYouth at their high schools were more likely to be male, younger, and at lower risk of developing eating disorders. In contrast, other recruitment channels (e.g., Internet, print materials) resulted in participants with significantly higher risk and symptom levels who used the program more frequently and with higher intensity. Conclusion: Efforts aimed at the dissemination of Internet-based interventions should consider the effects that different recruitment channels and access paths may have on sample composition and utilization of the intervention.